The Main Telescope of The Ulugbek Observatory (Texas Journal of Multidisciplinary Studies, 2022)
Our compatriots also made a great contribution to the study of celestial bodies. One of them is the grandson of Amir Temur Mirzo Ulugbek (1394-1449).